Analisis Wacana Kritis Model Teun A. Van Dijk pada Podcast Denny Sumargo “Mukjizat Tuhan, Terlahir Kembar Siam Dewi dan Putri Tidak Mau Dipisahkan” - Chornelyus Dehouq Simorangkir; Meylani Sitorus; Debi Margaret Kaloko; Rinaldi Nahampun; Sarma Panggabean (Universitas Islam Sumatera Utara, 2026)
This study aims to uncover the construction of meaning, ideological values, and social relations in Denny Sumargo’s podcast entitled “Mukjizat Tuhan, Terlahir Kembar Siam Dewi dan Putri Tidak Mau Dipisahkan.” The selection of this object is grounded in its rich humanitarian discourse and spiritual values that reflect broader social and cultural dimensions. The study addresses how meaning and ideology are constructed through discourse and how these elements shape social perceptions. Employing a qualitative descriptive approach, data were collected through observation and note-taking techniques and analyzed using Teun A. Van Dijk’s three-dimensional framework: text structure, social cognition, and social context. The findings reveal that diction, stylistic features, and narrative structures consistently construct an image of a religious, compassionate, and resilient family facing limitations. The podcast functions as a medium for conveying moral and spiritual messages, shaping public opinion and fostering social awareness through empathetic and reflective narratives. These results demonstrate that discourse in digital media plays a significant role in constructing meaning and influencing societal values.